EVALUATION OF BIO-PESTICIDES FOR POTATO TUBER MOTH CONTROL, PHTHORIMAEA OPERCULLELA (ZELLER) UNDER POLYHOUSE AND RUSTIC STORAGE CONDITIONS - Thakur, Meena; Chandla, V K (Potato Journal, 2013)
The potato tuber moth is a serious pest of potato, especially in stores, where the use of bio-pesticides or repellent plants is an environmentally sound alternative to chemical pesticides. Different bio-pesticides including PTM granulosis virus (GVPTM), Bacillus thuringiensis and locally available plant extracts (extracted in cow urine) were evaluated against this pest in storage and polyhouse conditions. Under storage conditions, although all the treatments were found significantly superior to control (57.08% tuber infestation) but among the treatments, GVPTM and Neemexcel were most effective (each with an average of 0.83% tuber infestation) followed by lantana camara (1.08%). Under different treatments, the numbers of infestation holes per tuber varied from 0.33 in GVPTM to 1.17 in Tegetes erectus; all being at par with each other, as compared to control (5.52 holes per tuber). In the storage, all the biopesticidal treatments afforded complete protection to potato tubers from the pest up to 15 days of treatment and were significantly superior even after 45 days of the treatment with an average tuber infestation ranging from 1.33-16.67% as compared to 89.33% in the control. Under poly house condition, the number of galleries per plant under different biopesticidal treatments varied from 0.43 to 1.27 which was lower than the economic threshold level (ETL) of 2 galleries per plant as compared to 5.57 galleries in control.